Study of folk taxonomy herb and spice plant in Guluk-Guluk Sumenep Madura as booklet for society - Fadhlan Muchlas Abrori (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Folk taxonomy is one of ethnobiological study. A study of conventional grouping of living creatures is still rarely conducted, thus, studying folk taxonomy is worthed. Living creatures grouping that has been done by society has a unique criterion that contributes in enriching information in ethnobiology field. The objective of this study is reviewing folk taxonomy in the Guluk-Guluk Region of Sumenep Madura and developing a booklet for the local community. The product of folk taxonomy study then been developed as a booklet that becomes one of information media for the society. The results showed that there are 39 species of herbs and spices. Zingiberaceae is the group with the largest number of species (6 species), that have been used by the society as spices and herbs, whereas the second largest number is Liliaceae with 5 species. The results of book review from the material expert, media expert and field test, were: 89.7%, 87.92%, and 87.06% respectively. These scores showed that the booklet is valid.